(untitled) (CAHIERS MAGELLANES-NS, 2024)
Systematic Investment Plan (SIP) of investment is one of the best strategies for salaried employees for personal financial growth. This method will lead to invest little amount every month or a regulated period by the investor for better returns in future. At the same time returns will be depends on selection of scheme or plan and moderate risks with subject to market fluctuations. Hence, the decision to invest through SIP requires a proper understanding of personal income and market situations. With this study there is an attempt for finding the perception of investors towards SIP investment for personal financial development.